BUSCLIS for construction industry - Noraziah, Ahmad; Mohammad Affendy, Omardin; Noriyani, Mohd Zin; Roslina, Mohd Sidek; Mohd Helmy, Abd Wahab; Ram, Jiwat (Springer, Berlin, Heidelberg, 2011)
In this research, we focus on software namely Building Submission Checklist System (BuSCLIS) that has been developed to be use in construction industry. An objective of developing BuSCLI is to simplify the management of submission data of building plan approval through online system for the Local Authority (LA) or State Town and Country Planning in Malaysia. We presents the data management of the system through the data dictionary include login, user, contractor, consultant, checklist, location and project. BuSCLI facilitates user by computerized the forms and provide fast, efficient, transparent, effective service to the engineer, architect and contractor. Relevant and timely information managed by sophisticated BuSCLI with the database management system, MySQL.